Training in ERCP and EUS in the UK anno 2017. Issue 2 (10th February 2017) - Bekkali, Noor LH; Johnson, Gavin J
Abstract : In the last 20 years, endoscopic retrograde cholangiopancreatography (ERCP) has evolved from being a diagnostic procedure to being almost exclusively therapeutic. Similarly, endoscopic ultrasound (EUS) is developing into ever-increasing therapeutic roles. Operator technique is central to diagnostic accuracy in EUS, as is effective and safer therapy for both ERCP and therapeutic EUS. Hence, effective training and robust standards for certification and revalidation are required to ensure ERCP and EUS in the UK are as effective and as safe as possible.